1996
DOI: 10.1002/j.1460-2075.1996.tb00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Escherichia coli RNA polymerase alpha subunit in modulation of pausing, termination and anti-termination by the transcription elongation factor NusA.

Abstract: The alpha subunit (alpha) of RNA polymerase (RNAP) is critical for assembly of polymerase and positive control of transcription initiation in Escherichia coli. Here, we report that alpha also plays a role in transcription elongation, and this involves a direct interaction between alpha and NusA factor. During in vitro transcription without NusA, alpha interacts with the nascent RNA, as revealed by photocrosslinking. When NusA is present, RNA crosslinks to NusA rather than to alpha. We show that this NusA‐RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 59 publications
2
58
0
1
Order By: Relevance
“…4 A and B). We propose that, in all organisms, regions A and B constitute the determinant for interaction with the , ho- (37) and to analysis of interactions of a with DNA, activators, repressors, and elongation factors (3)(4)(5)(6)(7)(8)(9). In principle, the procedures of this report should be generalizable to analysis of any multiprotein or nucleoprotein complex.…”
Section: Discussionmentioning
confidence: 97%
“…4 A and B). We propose that, in all organisms, regions A and B constitute the determinant for interaction with the , ho- (37) and to analysis of interactions of a with DNA, activators, repressors, and elongation factors (3)(4)(5)(6)(7)(8)(9). In principle, the procedures of this report should be generalizable to analysis of any multiprotein or nucleoprotein complex.…”
Section: Discussionmentioning
confidence: 97%
“…This pausing happens at specific transcript positions and for well-defined time intervals (ranging from 10 −6 sec to 10 sec). In bacteria, pausing can be due to interactions between the emerging RNA and the polymerase and/or polymerase-associated protein factors (Liu et al 1996;Landick 1997;Mooney et al 1998). The flavin mononucleotide (FMN)-dependent riboswitch in Bacillus subtilis (Wickiser et al 2005) is a beautiful example of how these features can be combined into a cotranscriptional feedback loop in which the binding of a metabolite selects one of two possible cotranscriptional folding pathways whose resulting RNA structure determines whether transcription is terminated or not.…”
Section: Transcription Transcription Speed and Variations Thereofmentioning
confidence: 99%
“…The NusA protein, which associates with elongating core RNA polymerase, interferes with this interaction (Liu and Hanna, 1995). Moreover, a mutation in the rpoA gene which suppresses the nusA1 mutation has been isolated, and deletion of the C-terminal domain of the ␣ subunit eliminated NusA enhancement of RNA polymerase pausing (Liu and Hanna, 1995;Liu et al, 1996;Schauer et al, 1996). Recently, it was demonstrated that the ␣CTD interacts directly with NusA and serves to stabilise the binding of NusA to core RNA polymerase (Liu et al, 1996).…”
Section: Figmentioning
confidence: 99%